2023
DOI: 10.1111/1751-7915.14207
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of abiotic factors on the fungal communities of ‘Honeycrisp’ apples in Canada

Abstract: The maintenance of the beneficial plant microbiome to control plant pathogens is an emerging concept of disease management, and necessitates a clear understanding of these microbial communities and the environmental factors that affect their diversity and compositional structure. As such, studies investigating the microbiome of economically significant cultivars within each growing region are necessary to develop adequate disease management strategies. Here, we assessed the relative impacts of growing season, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 69 publications
2
9
0
Order By: Relevance
“…When tissue-types are observed individually, growing season accounts for 67 and 74% of variations in the communities of core and peel tissues, respectively, providing further evidence that growing season impacts microbiome variation. On the whole, this corresponds to the observation in our previous study that the impact of the growing season was apparently greater on peel tissues than core tissues ( McLaughlin et al, 2023 ). Questions including how altering the macro-environmental conditions can impact tissue-specific micro-environments, and how these specific micro-environmental changes in turn are reflected in the microbiome, are likely important considerations if microbiome maintenance is to be seriously considered in disease management applications.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…When tissue-types are observed individually, growing season accounts for 67 and 74% of variations in the communities of core and peel tissues, respectively, providing further evidence that growing season impacts microbiome variation. On the whole, this corresponds to the observation in our previous study that the impact of the growing season was apparently greater on peel tissues than core tissues ( McLaughlin et al, 2023 ). Questions including how altering the macro-environmental conditions can impact tissue-specific micro-environments, and how these specific micro-environmental changes in turn are reflected in the microbiome, are likely important considerations if microbiome maintenance is to be seriously considered in disease management applications.…”
Section: Discussionsupporting
confidence: 91%
“…Further investigation of the factors influencing the fungal communities of specific fruit tissues will be necessary to identify the most relevant factors. In our previous studies we have observed similar trends of high microbial diversity in the core tissues compared to peel tissues ( Abdelfattah et al, 2021a ; McLaughlin et al, 2023 ).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The maintenance of the beneficial plant microbiome to control plant pathogens is an emerging concept of disease management, and necessitates a clear understanding of these microbial communities and the environmental factors that affect their diversity and compositional structure. Growing season is the most significant factor affecting fungal community structure and diversity of apple fruit, suggesting that future microbiome studies should take place for multiple growing seasons to better represent the host-microbiome of perennial crops under different environmental conditions [15].…”
mentioning
confidence: 99%